The Tricky Task of Fisher-Gardener Research in Conservation Paleobiology - Assumpção, Anna Clara Arboitte de; Caron, Felipe; Erthal, Fernando; Barboza, Eduardo Guimarães; Pinotti, Raphael Mathias; Ritter, Matias do Nascimento (Frontiers in Ecology and Evolution, 2022)
The study of sambaquis (ancient shell mounds) in conservation paleobiology is a complicated subject, especially when comparing body sizes of current and past mollusk valves to observe possible changes. There is a lack of information regarding how ancient fisher-gardeners collected these shellfish. Another obstacle is finding the hypothesis tests and data that can be used to compare current and past body sizes. To this end, we use the t-test (tt), Mann-Whitney (mw), and Bootstrap (bt) analyses to determine data scenarios for yellow clam (Amarilladesma mactroides) shells from two sambaquis units, and from two transects along the beaches of Rio Grande do Sul in southern Brazil. The study finds that the average body size of an Amarilladesma mactroides adult specimen is greater in sambaquis than the current valves across all tests (tt, p = 0.0005; mw, p = 0.006; bt, p = 0.04), even after reducing the sample number. However, when the comparison is only between valves that are larger than average, this does not hold true for two of the statistics (tt, p = 0.24; mw, p = 0.04; bt, p = 0.25). By refining the comparison for recent valves from different levels in the swash zone (upper, middle, and lower levels) with the past valves, we find that body sizes only differ at the middle level of the swash zone (tt, p = 0.004; mw, p = 0.004; bt, p = 0.005), where smaller adults, recruits, and juveniles live. This result could indicate that fisher-gardeners collected large organisms at distinct levels depending on the season (i.e., adults are collected in the upper level during summer and in the lower level during winter).